Effect of Staining and Bleaching protocol on Color Change of Bioactive Resin Composite Restorative Materials - Shara Ismael Sajini (Journal of Pharmacy and Bioallied Sciences)
Background: Dental bleaching is a common procedure to enhance aesthetics, but it often interacts with existing composite restorations. While previous studies focused on conventional composites, it is important to evaluate the impact of bleaching on emerging bioactive composites. Aims: To investigate the color change of two bioactive resin composites compared to a conventional one and the effect of two bleaching sessions (two cycles and three cycles) on the stained composite resins. Materials and Methods: Three light-cured resin composites—Tetric N-Ceram, Shade A2, Beauty II, shade A2, and Alkasite fluoride-releasing resin (Cention N)—were used for this study. Thirty sample discs were made. CIE, L*a*b* baseline color parameters were recorded by a lab-grade desktop spectrophotometer. The samples were in blueberry juice for 12 days. Fifteen samples were thermocycle and fifteen were bleached twice, each for three cycles. We estimated color change ΔE and whiteness index WID after thermocycling (Tt), before bleaching (T0), after the first bleaching session (T1), and after the second bleaching session (T2). Data was analyzed using one-way ANOVA, post-hoc Tukey’s test, and paired t-test (P < 0.05). Results: All composites exhibited detectable color changes after staining and thermocycling, with no significant differences between materials. Bleaching led to significant changes in color and WID across all samples, with Beautifil showing the most substantial change. Moreover, the differences between the first and second bleach were not significant except for Cention N. Conclusion: The effects of staining and bleaching were similar across different resin composites, but the whiteness index indicated significant changes, particularly for Beautifil samples.